1983
DOI: 10.1136/pgmj.59.687.46
|View full text |Cite
|
Sign up to set email alerts
|

Neurotensin-secreting carcinoma of the bronchus

Abstract: SummaryNeurotensin, a neuroendocrine peptide present in gut and brain has previously been found in pancreatic tumours secreting several other peptides. We report here the first case of a patient with a neurotensinsecreting adenocarcinoma of the bronchus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

1984
1984
1989
1989

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…It is conceivable that the immunoreactive material is released into the general circulation where it may be implicated in the pathogenesis of paraneoplastic syndromes. Previously, NTLI has been shown to be present in endocrine pancreatic tumours (Blackburn et al, 1980;Feurle et al, 1981;Gutniak et al, 1980;Theodorsson-Norheim et al, 1983) and it also was found in human small cell lung carcinomas (Wood et al, 1981(Wood et al, , 1983. At present, the only cell lines known to produce NTLI have been derived from a rat medullary carcinoma of the thyroid and a rat phaeochromocytoma (Tischler et al, 1982;Zeytinoglu et al, 1980).…”
Section: Resultsmentioning
confidence: 99%
“…It is conceivable that the immunoreactive material is released into the general circulation where it may be implicated in the pathogenesis of paraneoplastic syndromes. Previously, NTLI has been shown to be present in endocrine pancreatic tumours (Blackburn et al, 1980;Feurle et al, 1981;Gutniak et al, 1980;Theodorsson-Norheim et al, 1983) and it also was found in human small cell lung carcinomas (Wood et al, 1981(Wood et al, , 1983. At present, the only cell lines known to produce NTLI have been derived from a rat medullary carcinoma of the thyroid and a rat phaeochromocytoma (Tischler et al, 1982;Zeytinoglu et al, 1980).…”
Section: Resultsmentioning
confidence: 99%
“…Οι ασθενείς αυτοί είχαν αυξημένα επίπεδα VIP και νευροτενσίνης στο πλάσμα, ενώ η ναστρίνη, η σωματοστατίνη και το παγκρεατικό γλουκαγόνο ήταν φυσιολογικά. Τέλος, έκ κριση μόνο NTLI από βρογχικό αδενοκαρκίνωμα παρατηρήθηκε σε ασθενή με εκδηλώσεις υπερτροφικής πνευμονικής οστεοαρθροπάθειας, που μπο ρεί να προκλήθηκε από τη δράση της νευροτενσίνης στα αγγεία(203).Δύο μήνες πριν από την εκτέλεση των κυρίως πειραμάτων τοποθε τήθηκε στα πειραματόζωα ειδική συσκευή στο κρανίο, η οποία θα επέ τρεπε την εύκολη παρακέντηση της πλάγιας κοιλίας του ενκεφάλου για έγχυση ουσιών και λήψη δειγμάτων ΕΝΥ.Η συσκευή αποτελείται από δύο ορθογώνιες ανοξείδωτες μεταλλι κές πλάκες με δύο κοχλίες στη μία από αυτές, από μια σφαίρα από Tef lon και δύο περικόχλια" οι μεταλλικές πλάκες διαστάσεων 3X1.5X0.1 cm, έχουν κυκλικό άνοιγμα στο κέντρο, διαμέτρου 1 cm. Από τη σφαίρα αφαιρέθηκε ένα κωνικό τμήμα, ώστε να δημιουργηθεί ένα άνοιγμα σαν χω νί, από την κορυφή του οποίου ξεκινά λεπτός σωλήνας που καταλήγει στον αντίθετο πόλο της σφαίρας (Εικόνα 1).…”
unclassified